Approaches towards the synthesis of 7-halo-1, 2-dihydroxyindolizidines (7-halolentiginosines) thwarting Grob fragmentation processes. Issue 35 (2nd September 2015) - Vurchio, Carolina; Cordero, Franca M.; Faggi, Cristina; Macchi, Beatrice; Frezza, Caterina; Grelli, Sandro; Brandi, Alberto
Abstract: The synthesis of 7-halo-1, 2-dihydroxyindolizidines (7-halolentiginosines) starting from suitable protected 1, 2, 7-trihydroxyindolizidines (7-hydroxylentiginosines) has been studied. The results indicate a high propensity of the substrates to undergo fragmentation processes under standard halogenations conditions. The analysis of the products allowed an unprecedented full rationalization of Grob fragmentations processes in 7-substituted 1, 2-alkoxyindolizidines. Under optimized Appel reaction conditions 7-chloro- and 7-iodolentiginosines could be exclusively achieved (89–100% yields), whereas fluoruration was extremely sluggish and the 7-fluoro derivative was formed in only 19% through a two-step protocol. Biological assays proved that 7-fluoro- and 7-iodolentiginosines are endowed with proapoptotic activity analogously to (−)-lentiginosine and 7-hydroxylentiginosine. Graphical abstract: